Causes and effects of abuses in a feasibility study : a study in malaysian construction industry - Fong, Woan Shiuan (2013)
Feasibility study is essential to be carried out at the early stage of project life cycle before entering into actual construction works. However, there are abuses of feasibility study occurred in construction industry in which this issue is seldom being given attention by the developers. Hence, there are four objectives in this research that aims to be achieved, which include to identify the causes of abuses of feasibility study in construction industry, to determine the effects of abuses of feasibility study in construction industry, to highlight the types of abuses occurred in feasibility study in construction industry, and to examine the relationship between the causes and effects of abuses of feasibility study in construction industry. The respondents of this research are developers who are the REHDA (Real Estate and Housing Developers‘ Association) members in Johor, Malaysia. The research data are collected by using postal questionnaires to 109 developers in Johor, Malaysia. Statistical analysis is used for data analysis in this research. For achieving first three research objectives, mean frequencies are used, whereas for achieving the fourth research objective, Pearson correlation is used. The results of data analysis showed that there are occurrences of abuses of feasibility study where types of abuses occurred in feasibility study, causes and effects of abuses of feasibility study in construction industry are determined and ranked according to their mean frequencies. In addition, the findings of this research also showed that there are positive and significant relationships between the causes and effects of abuses of feasibility study. As conclusion, the developers and project team should aware of the issue of abuses of feasibility study in construction industry. Besides that, the developers and project team should also alert to the causes of abuses of feasibility study in order to avoid from suffering of bearing the effects of abuses of feasibility study in construction industry.